1984
DOI: 10.1128/aac.25.4.422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rifampin and bacitracin on nasal carriers of Staphylococcus aureus

Abstract: Anterior nares cultures from 664 hospital personnel identified 165 (24.8%) as carriers of Staphylococcus aureus. Persistent carriers (17.8%) were identified and randomly assigned to one of four treatment groups: rifampin (600 mg once a day for 5 days), bacitracin ointment (topically applied three times a day for 10 days), combined rifampin and bacitracin, and control (no treatment). Bacitracin ointment was ineffective in eliminating S. aureus from the anterior nares and had a postreatment carrier rate equal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 36 publications
0
14
0
3
Order By: Relevance
“…Neben Mupirocin wurden Bacitracin, Fusidinsäure oder Neomycin als topische Antibiotika zur nasalen Therapie eingesetzt [375][376][377][378][379]. Diese Antibiotika waren jedoch zum Teil nicht besser als das Placebo [376] oder wurden nur wenig untersucht [375,377].…”
Section: Nasale Dekolonisierungunclassified
See 1 more Smart Citation
“…Neben Mupirocin wurden Bacitracin, Fusidinsäure oder Neomycin als topische Antibiotika zur nasalen Therapie eingesetzt [375][376][377][378][379]. Diese Antibiotika waren jedoch zum Teil nicht besser als das Placebo [376] oder wurden nur wenig untersucht [375,377].…”
Section: Nasale Dekolonisierungunclassified
“…Diese Antibiotika waren jedoch zum Teil nicht besser als das Placebo [376] oder wurden nur wenig untersucht [375,377].…”
Section: Nasale Dekolonisierungunclassified
“…The rate of resistance is proportional to its use: from 1% of MRSA having acquired resistance to mupirocine after 5 days of decolonization up to 60% of resistant MRSA on areas treated several (wounds, nose, etc.) [32]. The authors of an American study assessed the cost-effectiveness of screening for nasal carriage every 3 months associated to a systematic treatment of all SA nasal carriers in hemodialyzed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have convincingly shown that colonization with S. aureus usually precedes infection (8,9) and that it can often be eradicated (10,11). In view of recent evidence in hemodialysis patients that control of S. aureus colonization can reduce the incidence of staphylococcal infections (10), it is important to detemine the factors predisposing to staphylococcal colonization in diabetic patients.…”
mentioning
confidence: 98%